Terapi Reperfusi Coronary Artery By Pass Grafting (CABG) Minimal Invasif dan Percutaneous Coronary Intervention (PCI) - I Gede Sumertana Jaya (Jurnal Kesehatan, 2023)
Reperfusion therapy in patients with Coronary Heart Disease (CHD) can be performed with the Percutaneous Coronary Intervention (PCI) procedure or a surgical procedure, namely Coronary Artery Bypass Grafting (CABG). Recently, CABG techniques have evolved to be less invasive, thus providing a more comfortable approach to the patient. This minimally invasive CABG procedure has a lower risk of restenosis and provides a better long-term quality of life compared to PCI. This research method is a literature review derived from the results of research that has been conducted and published in previous journals both nationally and internationally. The researchers searched these journals through journals that had been published in the database, namely PubMed, Mendeley, Cochrane Library and Google Scholar. Coronary heart disease (CHD) is a heart disease caused by narrowing of the coronary arteries due to atherosclerosis or spasm or a combination of both. The management that must be carried out in patients with CHD is reperfusion therapy consisting of Percutaneous Coronary Intervention (PCI), fibrinolytic therapy, and Coronary Artery Bypass Grafting (CABG). CABG is the gold standard in the management of patients with CHD where this procedure has a lower risk of restenosis and provides a better long-term quality of life compared to PCI. With the development of minimally invasive CABG techniques, it can provide better benefits for patients.